Ventilatory heterogeneity in the normal human lung is unchanged by controlled breathing - Prisk, G. Kim (J Appl Physiol (1985), 2020)
Measurement of ventilation heterogeneity with the multiple-breath nitrogen washout (MBW) is usually performed using controlled breathing with a fixed tidal volume and breathing frequency. However, it is unclear whether controlled breathing alters the underlying ventilatory heterogeneity. We hypothesized that the width of the specific ventilation distribution (a measure of heterogeneity) would be greater in tests performed during free breathing compared with those performed using controlled breathing. Eight normal subjects (age range = 23–50 yr, 5 female/3 male) twice underwent MRI-based specific ventilation imaging consisting of five repeated cycles with the inspired gas switching between 21% and 100% O(2) every ~2 min (total imaging time = ~20 min). In each session, tests were performed with free breathing (FB, no constraints) and controlled breathing (CB) at a respiratory rate of 12 breaths/min and no tidal volume control. The specific ventilation (SV) distribution in a mid-sagittal slice of the right lung was calculated, and the heterogeneity was calculated as the full width at half max of a Gaussian distribution fitted on a log scale (SV width). Free breathing resulted in a range of breathing frequencies from 8.7 to 15.9 breaths/min (mean = 11.5 ± 2.2, P = 0.62, compared with CB). Heterogeneity (SV width) was unchanged by controlled breathing (FB: 0.38 ± 0.12; CB: 0.34 ± 0.09, P = 0.18, repeated-measures ANOVA). The imposition of a controlled breathing frequency did not significantly affect the heterogeneity of ventilation in the normal lung, suggesting that MBW and specific ventilation imaging as typically performed provide an unperturbed measure of ventilatory heterogeneity. NEW & NOTEWORTHY By using MRI-based specific ventilation imaging (SVI), we showed that the heterogeneity of specific ventilation was not different comparing free breathing and breathing with the imposition of a fixed breathing frequency of 12 breaths/min. Thus, multiple-breath washout and SVI as typically performed provide an unperturbed measure of ventilatory heterogeneity.